A Bordism Viewpoint of Fiberwise Intersections - Gun Sunyeekhan (International Journal of Mathematics and Mathematical Sciences)
We use the geometric data to define a bordism invariant for the fiberwise intersection theory. Under some certain conditions, this invariant is an obstruction for the theory. Moreover, we prove the converse of fiberwise Lefschetz fixed point theorem.